Saturation in cascaded optical amplifier free-space optical communication systems - Bandele, Oluwatosin Jeremiah; Desai, Priyanka; Woolfson, Malcolm S.; Phillips, Andrew Julian (Institution of Engineering and Technology (IET), 2016)
The performance of a free-space optical (FSO) communication system in a turbulent atmosphere employing an optical amplifier (OA) cascade to extend reach is investigated. Analysis of both single and cascaded OA FSO communication links is given and the implications of using both adaptive (to channel state) and non-adaptive decision threshold schemes are analysed. The benefits of amplifier saturation, for example in the form of effective scintillation reduction when a non-adaptive decision threshold scheme is utilised at the receiver for different atmospheric turbulence regimes, are presented. Monte Carlo simulation techniques are used to model the probability distributions of the optical signal power, noise and the average bit error rate due to scintillation for the cascade. The performance of an adaptive decision threshold is superior to a non-adaptive decision threshold for both saturated and fixed gain preamplified receivers and the ability of a saturated gain OA to suppress scintillation is only meaningful for system performance when a non-adaptive decision threshold is used at the receiver. An OA cascade can be successfully used to extend reach in FSO communication systems and specific system implementations are presented. The optimal cascade scheme with a non-adaptive receiver would use frequent low gain saturated amplification.